FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIABETES MELLITUS PADA PASIEN RAWAT INAP DI RSUD BANGKINANG - Arifah, Arifah; Susmaneli, Herlina; Dewanto, Hoppy; Alamsyah, Agus; Kursani, Elmia (Ensiklopedia of Journal, 2024)
Diabetes Mellitus (DM) is an event, where glucose levels in the blood exceed normal limits. Diabetes mellitus cases are among the 10 highest incidences suffered by inpatients at Bangkinang Hospital, Kampar Regency in 2023. The purpose of this study is to find out whether there are factors related to the incidence of diabetes mellitus in inpatients at Bangkinang Hospital, Kampar Regency in 2023. The method of this research is quantitative with the type of observational analysis, cross sectional design and sampling techniques using simple random sampling, this study uses univariate and bivariate analysis. The study population is the total number of hospitalized patients (internal medicine) totaling 2667 patients, with a research sample of 183 patients. The results showed that there was a significant relationship between Hypertension (Pvalue = 0.001) and POR = 7.500; CI = (3,756-14,977) and Obesity (Pvalue = 0.001) with POR = 8,250; CI = (4,106-16,578) with the incidence of diabetes mellitus at Bangkinang Hospital, Kampar Regency in 2023. It is recommended to the hospital to be able to provide education to inpatient patients who are not DM sufferers to avoid and control weight and blood pressure to avoid DM disease, and for DM patients so that it does not get worse.Keywords: Diabetes Mellitus, Hypertension, Obesity